Cellular density and variability in laryngeal and pharyngeal squamous cell carcinoma using confocal laser endomicroscopy - Sievert, Matti; Aubreville, M.; Eckstein, Markus; Mantsopoulos, Konstantinos; Koch, Matthias; Gostian, Antoniu-Oreste; Müller, Sarina Katrin; Iro, Heinrich; Goncalves, M. (European Review for Medical and Pharmacological Sciences, 2023)
OBJECTIVE: Confocal laser endomicroscopy (CLE) allows the visualization of epithelium in a thousand-fold magnification. This study analyzes the architectural differences at the cellular level of the mucosa and squamous cell carcinoma (SCC). PATIENTS AND METHODS: A total of 60 CLE sequences recorded in 5 patients with SCC undergoing laryngectomy between October 2020 and February 2021 were analyzed. The corresponding histologic sample derived from H&E staining was assigned to each sequence, capturing CLE images of the tumor and healthy mucosa. In addition, the cellular structure analysis was performed to diagnose SCC by measuring the total number of cells and cell size in 60 sequences in a fixed field of view (FOV) with 240 μm in diameter (45,239 μm2). RESULTS: Out of 3,600 images, 1,620 (45%) showed benign mucosa and 1,980 (55%) SCC. The automated analysis yielded a difference in cell size, with healthy epithelial cells being 171.9±82.0 μm2 smaller than SCC cells, which were 246.3±171.9 μm2 and showed greater variability in size (p=0.037). In addition, due to the probe’s fixed FOV, there was a difference in cell count with a total of 188.7±38.3 and 124.8±38.6 cells in images of normal epithelium and SCC (p<0.001), respectively. Regarding cell density as a criterion for the differentiation of benign/malign, using a cut-off value of 145.5 cells/FOV, we obtained sensitivity and specificity of 88.0% and 71.9%, respectively. CONCLUSIONS: SCC reveals marked differences at a cellular level compared to the healthy epithelium. Our results further support the importance of this feature for identifying SCC during CLE imaging.
CRIS-Team Scopus Importer:2023-05-26
Keywords: Classification; Confocal laser endomicroscopy; Head and neck squamous cell carcinoma; Larynx; Optical biopsy; Pharynx